A Randomized Pilot Study of Aortic Waveform Guided Therapy in Chronic Heart Failure. Issue 2 (20th March 2014) - Borlaug, Barry A.; Olson, Thomas P.; Abdelmoneim Mohamed, Sahar; Melenovsky, Vojtech; Sorrell, Vincent L.; Noonan, Kelly; Lin, Grace; Redfield, Margaret M.
Abstract : Background: Medication treatment decisions in heart failure (HF) are currently informed by measurements of brachial artery pressure, but ventricular afterload is more accurately represented by central aortic pressure, which differs from brachial pressure. We sought to determine whether aggressive titration of vasoactive medicines beyond goal‐directed heart failure medical therapy (GDMT) based upon aortic pressure improves exercise capacity and cardiovascular structure‐function. Methods and Results: Subjects with chronic HF (n=50) underwent cardiopulmonary exercise testing, echocardiography, and arterial tonometry to measure aortic pressure and augmentation index, and were then randomized to aortic pressure‐guided treatment (active, n=23) or conventional therapy (control, n=27). Subjects returned for 6 monthly visits wherein GDMT was first optimized. Additional vasoactive therapies were then sequentially added with the goal to reduce aortic augmentation index to 0% (active) or if brachial pressure remained elevated (control). Subjects randomized to active treatment experienced greater improvement in peak oxygen consumption compared with controls (1.37±3.76 versus −0.65±2.21 mL min −1 kg −1, P =0.025) though reductions in aortic augmentation index were similar (−7±9% versus −5±6%, P =0.46). Forward stroke volume increased while arterial elastance and left ventricular volumes decreased in all participants, with no between‐group difference. Subjects randomized to active treatment were more likely to receive additional vasoactive therapies including nitrates, aldosterone antagonists and hydralazine, with no increased risk of hypotension or worsening renal function. Conclusions: Maximization of goal‐directed medical therapy in heart failure patients may enhance afterload reduction and lead to reverse remodeling, while additional medicine titration based upon aortic pressure data improves exercise capacity in patients with heart failure.